2013
DOI: 10.5339/gcsp.2013.25
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular mechanics in hypertrophic cardiomyopathy using feature tracking

Abstract: Objectives: Right ventricular (RV) mechanics in hypertrophic cardiomyopathy (HCM) are poorly understood. We investigate global and regional deformation of the RV in HCM and its relationship to LV phenotype, using 2D strain vector velocity imaging (VVI). Methods: 100 HCM patients (42% females, 41 ± 19 years) and 30 control patients were studied using VVI. Longitudinal peak systolic strain (ϵsys), strain rate (SR), time to peak (ϵ) (TTP), displacement of RV free wall (RVFW) and septal wall were analyzed. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Although RV strain is not as widely used as LV strain, we and others [ 21 ] have found RV strain to be highly reproducible using CMR tissue tracking. As with RVEF (although small reduction), RV longitudinal strain was impaired in HCM patients, a finding consistent with previous echocardiographic studies [ 32 34 ]. Additionally, we show that on CMR, RV circumferential and radial strain were also reduced in HCM patients.…”
Section: Discussionsupporting
confidence: 91%
“…Although RV strain is not as widely used as LV strain, we and others [ 21 ] have found RV strain to be highly reproducible using CMR tissue tracking. As with RVEF (although small reduction), RV longitudinal strain was impaired in HCM patients, a finding consistent with previous echocardiographic studies [ 32 34 ]. Additionally, we show that on CMR, RV circumferential and radial strain were also reduced in HCM patients.…”
Section: Discussionsupporting
confidence: 91%
“…Since none of our patients had isolated apical HCM, we take this finding as potential subclinical involvement of RV apex with the HCM pathology. A similar loss of RV strain from base to apex in patients with HCM disease was also reported by Badran et al [30]. In contrast, cardiac amyloidosis seems to initially affect the basal parts of the LV, as seen by lower strain values in the basal segments [31,32].…”
Section: Discussionsupporting
confidence: 83%
“…Over the last 50 years, awareness regarding the characterization of HCM has evolved dramatically in terms of phenotypic expression, pathophysiology, and clinical course [ 19 – 21 ]. It is reasonable that the right ventricle may participate in the disease due to the extension of myopathic processes and/or because right and left ventricles share structurally hypertrophied interventricular septum [ 22 ]. Previous experimental and clinical studies indicate that the septum is ‘the lion of the right ventricular function’ and the fiber orientation and septal architecture and function are essential for RV ejection and suction for rapid filling [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an echocardiographic study, Cincin et al reported significant impairment of RV function and 2D-STE-based strain of the RV free wall basal segment in HCM adults in comparison to control subjects [ 28 ]. Moreover, Badaran et al used vector velocity imaging and showed severe displacement incorrectness at all levels of RV in HCM adults [ 22 ]. Our study is the first to demonstrate an impairment of RV mechanics in the childhood HCM population by means of CMR-FT. Our results of CMR-FT-derived RVGLS are slightly higher than the values obtained with echocardiography in adults [ 29 ].…”
Section: Discussionmentioning
confidence: 99%